Interleukin-1 receptor 1 deletion in focal and diffuse experimental traumatic brain injury in mice - Chung, Joon Yong; Krapp, Nicolas (Journal of neurotrauma, 2019)
Important differences in the biology of focal and diffuse traumatic brain injury (TBI) subtypes may result in unique pathophysiological responses to shared molecular mechanisms. Interleukin-1 (IL-1) signaling has been tested as a potential therapeutic target in preclinical models of cerebral contusion and diffuse TBI, and in a phase II clinical trial, but no published studies have examined IL-1 signaling in an impact/acceleration closed head injury (CHI) model. We hypothesized that genetic deletion of IL-1 receptor-1 (IL-1R1 KO) would be beneficial in focal (contusion) and CHI in mice. Wild type and IL-1R1 KO mice were subjected to controlled cortical impact (CCI), or to CHI. CCI produced brain leukocyte infiltration, HMGB1 translocation and release, edema, cell death, and cognitive deficits. CHI induced peak rotational acceleration of 9.7 × 105 ± 8.1 × 104 rad/s2, delayed time to righting reflex, and robust Morris water maze deficits without deficits in tests of anxiety, locomotion, sensorimotor function, or depression. CHI produced no discernable acute plasmalemma damage or cell death, blood-brain barrier permeability to IgG, or brain edema and only a modest increase in brain leukocyte infiltration at 72 h. In both models, mature (17 kDa) interleukin-1 beta (IL-1β) was induced by 24 h in CD31+ endothelial cells isolated from injured brain but was not induced in CD11b+ cells in either model. High mobility group box protein-1 was released from injured brain cells in CCI but not CHI. Surprisingly, cognitive outcome in mice with global deletion of IL-1R1 was improved in CHI, but worse after CCI without affecting lesion size, edema, or infiltration of CD11b+/CD45+ leukocytes in CCI. IL-1R1 may induce unique biological responses, beneficial or detrimental to cognitive outcome, after TBI depending on the pathoanatomical subtype. Brain endothelium is a hitherto unrecognized source of mature IL-1β in both models.